Analyzing the Frame Model of MAIDAN-concept (Case Study of British Internet-Media Corpus) - Yehorova, Olesya Ivanivna; Stepanov, Vitaly Valerijovych (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The current study represents an attempt to build a model of frame representation of MAIDAN-concept which is analyzed in terms of its cause and contact interactions with its concomitant concept GOVERNMENT. The model relies on the discourse material of British Internet mass media and is represented from the perspective of four basic frames (Thing, Action, Comparison and Identification Frames). Along with the broad notion of “frame”, the article considers the notions of “frame-script” and “frame-plan”, highlights their deviations, and defines the status of the analyzed concept MAIDAN.